2002
DOI: 10.1016/s0020-7292(02)00237-0
|View full text |Cite
|
Sign up to set email alerts
|

Infertility in rural Ghana

Abstract: Infertility in Ghana and other sub-Saharan countries deserves more recognition as a public health problem. Prevention and treatment of infertility should be incorporated in reproductive health programs, while male participation in reproductive health programs and research needs to be encouraged. Public education about the causes of infertility is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 8 publications
1
40
0
Order By: Relevance
“…The finding was different from studies in South Africa, Saudi Africa and Pakistan (5,16,32) where the majority believed the couple should present for investigation and management together. However, our findings are similar to those in studies undertaken in Gambia and Ghana (10,33) which found that women alone were the ones seeking care whether in orthodox or traditional medicine outlets. The majority of our respondents (71.7%) had sought care from traditional and spiritual healers for infertility before presenting to the hospitals.…”
Section: Resultssupporting
confidence: 90%
“…The finding was different from studies in South Africa, Saudi Africa and Pakistan (5,16,32) where the majority believed the couple should present for investigation and management together. However, our findings are similar to those in studies undertaken in Gambia and Ghana (10,33) which found that women alone were the ones seeking care whether in orthodox or traditional medicine outlets. The majority of our respondents (71.7%) had sought care from traditional and spiritual healers for infertility before presenting to the hospitals.…”
Section: Resultssupporting
confidence: 90%
“…In Qatar, the prevalence of secondary infertility (19.1%) was higher in Qatari men with DM as compared to primary infertility (16%). Several epidemiologic studies have demonstrated an increased risk for infertility in diabetic men [15][16][17][18]. These Fig.…”
Section: Discussionmentioning
confidence: 90%
“…In sub-Saharan Africa, the prevalence differs widely from 9% in the Gambia (Sundby et al ., 1998) and 11.8% in Ghana (Geelhoed et al ., 2002) compared with 21.2% in northwestern Ethiopia (Haile, 1990) and between 20 and 30% in Nigeria (Ebomoyi and Adetoro, 1990; Adetoro and Ebomyi, 1991; Okonofua, 1996; Larsen, 2000). Even less data are available from Asia and Latin-America, but a report compiled by the World Health Organization (WHO) indicated that the prevalence of infertility in these regions fell within the globally expected range 8–12% of couples of reproductive age and was thus lower when compared with African countries (World Health Organization, 1991).…”
Section: Prevalence Of Infertility In Developing Countriesmentioning
confidence: 99%